Book Review: Applications of Ion Exchange Materials in Chemical and Food Industries - Balla, Putrakumar; Ginjupalli, Srinivasa R.; Pothu, Ramyakrishna; Boddula, Rajender; Perugopu, Vijayanand (Current Analytical Chemistry, 2022)
A Book entitled Applications of Ion Exchange Materials in published by Chemical and Food Industries Edited by Inamuddin, Abdullah M. Asiri, and Tauseef Ahmad Rangreez, Springer, in 2019, (Print ISBN 978-3-030-06084-8, ISBN 978-3-030-06085-5, DOI: 10.1007/978-3-030-06085-5). This book provides an up-to-date, complete overview of various applications of ion exchange resins in the chemical and food industry. The chemistry of ion exchange resin materials towards its allied applications, including deionization, dealkalization, dehydration, hydrogenation, esterification, reactive separation, synthesis, separation, and purification of industrial products, were well addressed in this book, along with drawbacks and future scope to improve for better performance on the industrial scale. This book consists of nine chapters. Altogether, they discuss the applications of ion exchange resins in solid acid catalysis, reaction separation, removal, and recovery of metals in chemical reactions, and preparation of Ag-aggregated ion-exchanged silicates, specifically as it is not possible to discuss each and everything in detail. The chapters are presented effectively by reputed experts around the world. That makes this book an exceptionally significant and authentic source of information. It is valuable for a book to provide updated information, review the work done to date, do proper analysis, compare the pros and cons of comparable existing technologies, and guide the reader to research gaps and places where improvement is required. This book is an essential reference guide for students, researchers, engineers, professionals, and industrial research and development specialists in chemistry, chemical and biochemical technology, food chemistry, synthetic chemistry, and industrial chemistry.
Keywords: thermal annealing